Why do journals discontinue? A study of Australian ceased journals. Issue 2 (14th February 2022) - Jamali, Hamid R.; Wakeling, Simon; Abbasi, Alireza
Abstract: Little is known about why journals discontinue despite its significant implications. We present an analysis of 140 Australian journals that ceased from 2011 to mid‐2021 and present the results of a survey of editors of 53 of them. The death age of journals was 19.7 (median = 16) with 57% being 10 years or older. About 54% of them belonged to educational institutions and 34% to non‐profit organizations. In terms of subject, 75% of the journals belonged to social sciences, humanities and arts. The survey showed that funding was an important reason for discontinuation, and lack of quality submission and lack of support from the owners of the journal also played a role. Too much reliance on voluntary works appeared to be an issue for editorial processes. The dominant metric culture in the research environment and pressure for journals to perform well in journal rankings negatively affect local journals in attracting quality submissions. A fifth of journals indicated that they did not have a plan for the preservation of articles at the time of publication and the current availability of the content of ceased journals appeared to be sub‐optimal in many cases with reliance on the website of ceased journals or web‐archive platforms.